De krokodil en de verdronken dienstmaagd: Székely-Lulofs in Deli en Boedapest - Okker, Frank (Acta Neerlandica, 2016)
Between the first own household of Madelon Székely-Lulofs – the well-known writer from the Dutch East Indies – in the arable region of Deli (on the east coast of Sumatra) and her home, later on, in the centre of Budapest one can notice a number of striking parallels. In both places the grinding lack of money, the care for the right food, her contact with the servants and a huge crocodile played a prominent role.